Rh(III)-Catalyzed Synthesis of 2-Nitro-2H-azirines via sp3 C–H Activation - Huang, Xiaojun; Ge, Yun; Qian, Yang; Zhang, Zhengyu (Synlett, 2022)
An expedient Rh(III)-catalytic method has been described to synthesis of 2-nitro-2H-azirine derivatives from easily accessible β-nitrooxime ethers via sp3 C–H activation process. This protocol features of low catalyst loading, very mild reaction conditions, and tolerating a diverse of functionalities in good yields. A possible reaction pathway is proposed involving [RhCp*Cl2]2-catalyzed sp3 C–H bond activation and pivalic acid elimination steps.
Keywords: Rh(III); 2-nitro-2H-azirine; derivatives; β-nitrooxime; sp3 C–H